2018
DOI: 10.1155/2018/9465784
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Adiposity Level, Metabolic Syndrome, and Insulin Resistance for the Risk of Nonalcoholic Fatty Liver Disease Diagnosis in Obese Children

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in obese children. Early diagnosis and treatment are essential for curing or slowing down the disease progression. The aim of the study was to assess the prevalence of NAFLD in this population and to identify anthropometrical and metabolic risk factors for NAFLD prediction and its development. Material and Methods The study included 108 obese children. Anthropometric measurements, NAFLD diagnosis (based on ALT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
(59 reference statements)
4
25
0
Order By: Relevance
“…By recruiting 254 children and adolescents aged 6–17 years, Patton et al (79) have demonstrated that the severity of IR was significantly correlated with histological features of NAFLD and the risk of MetS was greater among those with severe steatosis. In accordance with previous studies (40, 80), Prokopowicz et al (81) observed an impaired metabolic profile, characterized by greater waist circumference, IR, glucose dysregulation, and dyslipidemia in 45% of overweight adolescents with hepatic steatosis than children without. Moreover, 40.8% of children with NAFLD presented MetS.…”
Section: Common Pathogenetic Mechanisms Linking Nafld and Metssupporting
confidence: 87%
“…By recruiting 254 children and adolescents aged 6–17 years, Patton et al (79) have demonstrated that the severity of IR was significantly correlated with histological features of NAFLD and the risk of MetS was greater among those with severe steatosis. In accordance with previous studies (40, 80), Prokopowicz et al (81) observed an impaired metabolic profile, characterized by greater waist circumference, IR, glucose dysregulation, and dyslipidemia in 45% of overweight adolescents with hepatic steatosis than children without. Moreover, 40.8% of children with NAFLD presented MetS.…”
Section: Common Pathogenetic Mechanisms Linking Nafld and Metssupporting
confidence: 87%
“…Differences between the results of these studies (>9 years old) and the present study (<9 years old) might have resulted from differences in the age of study participants, as well as in the severity of steatosis (in the present study, only grade I vs. minimal-to-severe fatty liver or even beginning non-alcoholic steatohepatitis (NASH) in other studies) and obesity of participants enrolled [ 5 , 38 ]. The study setting (here, children recruited in schools vs. hospitals in most other studies) and markers used to assess insulin resistance (in the present study, fasting glucose and insulin vs. oral glucose tolerance tests) were also markedly different between these studies and the present study [ 5 , 38 , 39 ]. Reasons for the significantly higher levels of total cholesterol and LDL cholesterol in the sera of overweight children without NAFLD have to be delineated in future studies.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, the apparent lack of relation of waist circumference and the ratio of adiponectin to leptin might be related to the rather young age of study participants (<9 years) and to differences in subcutaneous adipose tissue mass rather than visceral adipose tissue. Furthermore, results of others also suggested that overweight children with hepatic steatosis have a higher BMI and waist circumference when compared to overweight children without signs of NAFLD [ 5 , 38 , 39 ]. Previous studies of others also reported that transaminase activities in the sera of overweight children were also similar to those of overweight children serving as controls [ 38 ]; however, in contrast to the findings of the present study, in studies of others, a strong association of the presence of NAFLD in overweight children with increased markers of insulin resistance, dyslipidemia, and the presence of metabolic abnormalities was found [ 5 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the additional time and cost required for an OGTT, the feature selection steps were reapplied to a subset of clinical phenotype variables not including OGTT measurements, and this revealed that WC, HOMA‐IR, and blood triglycerides had the greatest capability to identify NAFLD. This was not surprising because although HOMA‐IR and WBISI are calculated using different information, i.e., fasting versus OGTT‐based glucose and insulin measurements, respectively, both are generally reflective of an individual’s degree of insulin resistance, which is often a co‐occurring morbidity with NAFLD and has been shown in prior studies to be predictive of NAFLD among children with obesity …”
Section: Discussionmentioning
confidence: 99%